2014
DOI: 10.1111/ele.12253
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between constitutive and induced defences drive geographical and climatic clines in pine chemical defences

Abstract: There is increasing evidence that geographic and climatic clines drive the patterns of plant defence allocation and defensive strategies. We quantified early growth rate and both constitutive and inducible chemical defences of 18 Pinaceae species in a common greenhouse environment and assessed their defensive allocation with respect to each species' range across climatic gradients spanning 31° latitude and 2300 m elevation. Constitutive defences traded-off with induced defences, and these defensive strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
250
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 204 publications
(268 citation statements)
references
References 46 publications
(142 reference statements)
14
250
3
1
Order By: Relevance
“…1B). In support of this hypothesis, Moreira et al (2014) found that constitutive and induced levels of defensive resins traded off among pine species, and an elevational gradient among species was observed for constitutive (but not induced) resins, with these defences increasing with elevation. Similarly, tradeoffs between tolerance and resistance have also been reported in other temperate plantinsect herbivore interactions (Fineblum andRausher 1995, Agrawal et al 1999) and are thus expected to tradeoff along elevational gradients.…”
Section: Box 1 Definition Of Plant Defensive Strategiesmentioning
confidence: 64%
See 2 more Smart Citations
“…1B). In support of this hypothesis, Moreira et al (2014) found that constitutive and induced levels of defensive resins traded off among pine species, and an elevational gradient among species was observed for constitutive (but not induced) resins, with these defences increasing with elevation. Similarly, tradeoffs between tolerance and resistance have also been reported in other temperate plantinsect herbivore interactions (Fineblum andRausher 1995, Agrawal et al 1999) and are thus expected to tradeoff along elevational gradients.…”
Section: Box 1 Definition Of Plant Defensive Strategiesmentioning
confidence: 64%
“…Consequently, plant species adapted to environments with limiting abiotic conditions are predicted to increase allocation to expensive constitutive defences (relative to induced defences), as the energy demand of replacing tissues consumed by insect herbivores is higher under such stressful conditions (Moreira et al 2014, Pellissier et al 2016 (Fig. 1B).…”
Section: Box 1 Definition Of Plant Defensive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest it may relate to delayed induced defense responses (47). Induced defenses are critical during bark beetle outbreaks (35), are under genetic control (48) and, importantly, often show a trade-off with constitutive defenses (49). Therefore, higher constitutive defenses in faster growing trees and families at our site (45, 50) may be associated with lower induced defenses.…”
Section: Discussionmentioning
confidence: 84%
“…Some tree species have resin canals filled with (constitutive) resin, which is transported to and released at wounded spots upon wounding, other species start producing (induced) resin after wounding and may require more time for defence against invaders (Lewinsohn et al, 1991;Trapp and Croteau, 2001) and some species can produce both constitutive and induced resin (Raffa and Berryman, 1982;Lombardero et al, 2000;Franceschi et al, 2005). Overall, the resin secretory structures and the type of resin (constitutive or induced) used for defence is largely species specific (Moreira et al, 2014). Recent evidence show that Boswellia trees have constitutive resin, but probably also produce induced resin upon wounding trees for frankincense harvest (Tolera et al, 2013a;Eshete et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%